A Bridge from Behind Bars: A Look at Prison Literacy Programs1 - Dominique T. Chlup; Irene C. Baird (Adult Education Research Conference, 2010)
The purpose of this paper is to illustrate—using four U.S. based case examples—how writing and literacy education practices are connected to prisoner self-reflection, knowledge development, and re-visioning of prisoner lives. While we explore prisons as sites for literacy education, we also complicate the picture by acknowledging that education for prisoners needs to go beyond adult basic education and literacy.